2020
DOI: 10.1038/s41598-020-74409-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of early neurodevelopmental disorders associated with in utero exposure to valproate and other antiepileptic drugs: a nationwide cohort study in France

Abstract: Information available on the risks of neurodevelopmental disorders (NDs) associated with in utero exposure to valproate (VPA) and to other antiepileptic drugs (AEDs) is limited. A nationwide population-based cohort study was conducted based on comprehensive data of the French National Health Data System (SNDS). Liveborn infants without brain malformation, born between January 2011 and December 2014, were followed from birth up to December 2016. NDs were identified based on diagnoses of mental or behavioural di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 43 publications
5
53
1
Order By: Relevance
“…Our limited findings regarding dose, in addition to existing literature investigating dose associations between newer ASMs and congenital malformations, 2 suggest that larger samples, utilizing ASM blood levels, will be needed to detect dose‐dependent effects in newer ASMs. Studies will need to consider exposure throughout the entire duration of gestation, while noting the importance of the late second and third trimester for fetal brain development 56 . Outcomes will also vary by maternal and fetal genotypes, 57 which alter susceptibility to the ASM exposure; large populations of ASM‐exposed children are necessary to address this and will likely require international collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Our limited findings regarding dose, in addition to existing literature investigating dose associations between newer ASMs and congenital malformations, 2 suggest that larger samples, utilizing ASM blood levels, will be needed to detect dose‐dependent effects in newer ASMs. Studies will need to consider exposure throughout the entire duration of gestation, while noting the importance of the late second and third trimester for fetal brain development 56 . Outcomes will also vary by maternal and fetal genotypes, 57 which alter susceptibility to the ASM exposure; large populations of ASM‐exposed children are necessary to address this and will likely require international collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these effects were stronger when exposures occurred during the second and third trimesters of pregnancy. However, these findings were not affected by the mother’s mental health 213 .…”
Section: Translational Aspects and Concluding Remarksmentioning
confidence: 71%
“…In the case of VPA, human evidence supports only a poor interaction between the effects of prenatal exposure to VPA and maternal mental health. Thus, a very recent nationwide population-based analysis has shown that in utero exposure to VPA is associated with an increased risk of neurodevelopmental mental and behavioral disorders in exposed children 213 . Moreover, these effects were stronger when exposures occurred during the second and third trimesters of pregnancy.…”
Section: Translational Aspects and Concluding Remarksmentioning
confidence: 99%
“…Observational studies are therefore essential to study the efficacy and safety drugs in pregnant women and their offspring. For instance, a French nationwide study on recent data confirmed that valproic acid, a treatment for epilepsy, cause birth defects and delayed cognitive development [ 2 , 3 ].…”
Section: Background and Aimsmentioning
confidence: 99%